Navier-Stokes Equations with Potentials. (3rd June 2007) - Lefter, Adriana-Ioana
Abstract : We study Navier-Stokes equations perturbed with a maximal monotone operator, in a bounded domain, in 2D and 3D. Using the theory of nonlinear semigroups, we prove existence results for strong and weak solutions. Examples are also provided.